Manajemen Supervisi Pengawas Untuk Meningkatkan Kinerja Kepala Madrasah Tsanawiyah Swasta - Dadang Supriadi (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
This research is motivated by the importance of the role of madrasah supervisors in providing effective supervision to improve the quality of madrasah principals' performance, especially in private Madrasah Tsanawiyah environments. Supervisory supervision not only functions as a quality control tool, but also as a means of coaching, mentoring, and empowering madrasah principals in carrying out managerial, leadership, and school development tasks. The purpose of this study is to analyze how supervisory supervision management can improve the performance of private Madrasah Tsanawiyah principals, as well as to identify the most relevant supervision strategies in supporting the achievement of educational quality. The research method used is a qualitative approach with data collection techniques through interviews, observations, and documentation, which are then analyzed descriptively. The results of the study indicate that the implementation of planned, systematic, and continuous supervisory management has a positive effect on improving the competency of madrasah principals in the aspects of planning, program implementation, and educational evaluation. The findings also show that participatory and communicative supervision can build motivation and a sense of responsibility of madrasah principals in managing institutions effectively. The implication of this research is the need to improve the capacity of madrasah supervisors through training and role strengthening so that supervision can truly drive optimal madrasah principal performance, thus impacting the quality of education in private junior high madrasahs.